Security mediated certificateless signatures - Yap, Nvun-She; Chow, Sherman S. M.; Heng, Swee-Huay; Goi, Bok-Min (Springer Berlin Heidelberg, 2007)
In PKC 2006, Chow, Boyd and Gonzalez Neito introduced the notion of security mediated certificateless (SMC) cryptography. SMC cryptography equips certificateless cryptography with instantaneous revocation. They presented a formal security model with two constructions for SMC encryption. This paper studies SMC signatures. We first present :3, security analysis of a previous attempt by Ju et al. in constructing a SMC signature scheme. We then formalize the notion of SMC signatures and propose the first concrete provable scheme without bilinear pairing. Our scheme is existential unforgeable in the random oracle model based on the intractability of the discrete logarithm problem, has a short public key size, and achieves a trust level which is the same as that of a traditional public key signature.